Application of the Problem Based Learning Model to Increase the Motivation to Learn Mathematics in Grade IV Elementary School Students - Wiyandari, Husnul Fathonah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Low student learning motivation can hinder the achievement of learning objectives and must be handled appropriately. Things that can be developed by the teacher to overcome the problem of learning motivation in students by applying an innovative learning model that emphasizes student activity. The purpose of this study was to increase students' learning motivation in Mathematics in grade IV Elementary Schools with the Problem Based Learning (PBL) learning model. The research conducted was Classroom Action Research (PTK) in two cycles. The instrument used was an observation sheet of students' learning motivation with 4th grade subjects totaling 20 students. Based on the results of the study there was an increase in learning motivation from the pre-cycle of 40% then increased in each cycle, the first cycle was 73% and the second cycle was 87%. These results indicate that using the Problem Based Learning (PBL) learning model is proven to be able to increase students' learning motivation.